ANALISIS MORFOTEKTONIK SESAR LEMBANG, JAWA BARAT - Edi Hidayat (Widyariset, 2010)
The Lembang fault was located approximately 10 km to the north of Bandung City that crossed the Kecamatan Lembang City directe in east-west direction for 22 km length. The existence of this fault became very important because this fault crossed the densely-populated settlement and tourism area. Up to now, the level of the activity of this fault was still in matter of debate due to the insufficient of seismicity data and history resulted by the activation of this fault. One of the approaches to determine the level of the activity of the Lembang Fault is morphometry analysis. Paramater used to morphometry analysis comprise of ratio of valley floor width to valley height (Vf) and drainage basin asymmetry (AF). In addition to morphometry, sediment analysis sagpond also used to determine the fault activity. Result analysis of the two methods above, indicates that the Lembang an active fault with the movement down (normal fault).